أوجه القصور في الصياغة التشريعية لقوانين الوظيفة العامة: دراسة تطبيقية في القوانين الصادرة في ظل دستور 2005 - جعفر رشا محمد (Journal of Legal Sciences, 2019)
The issuance of the current Constitution rejoiced jurists issuance of several legal reforms, particularly in the civil field, the importance of public service as a commissioned a national social service targets based out of public interest and serve the citizens in the light of the laws in force and this provision consistent with the provisions of the Constitution in force, they serve a special kind of aims to achieve the public interest and is composed of the powers, duties and responsibilities entrusted to the employee legally performed in accordance with the objectives of the department to serve the public interest. It is not a privilege for those who are enrolled or a favor to the masses, because the employee of the citizens and the duty imposed by law upon service and hold him accountable if breached. Due to the development in the public service as it provides many of the tools used by the administration in order to evaluate crooked behavior and disclosure of financial and administrative irregularities and crimes committed by employees and reporting the results to be reached for the competent authorities to take appropriate action, we note the issuance of laws and rules that regulate the function is continuously to keep pace with the times and keep up with the evolution of legal development for the public service, filling the void deficiencies and to develop legislation and laws and constantly updated. We discussed this constitutes an attempt to detect the most prominent shortcomings, which included these laws.